2019
DOI: 10.1371/journal.pone.0221081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for latent tuberculosis infection among healthcare workers in Morocco

Abstract: Increased prevalence of latent tuberculosis infection (LTBI) has been observed among high-risk populations such as healthcare workers (HCWs). The results may depend on the method of LTBI assessment, interferon-gamma release assay (IGRA) and/or tuberculin skin test (TST). Here, we investigated the prevalence and risk factors for LTBI assessed by both IGRAs and TST in HCWs living in Morocco, a country with intermediate tuberculosis (TB) endemicity and high BCG vaccination coverage. HCWs were recruited in two Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
2
18
1
3
Order By: Relevance
“…The healthcare workers who work in the pulmonary disease service units have a fourfold increased risk of LTBI compared to the non-clinical service units. 47 This is related to the characteristics of pulmonary TB, which is easily transmitted from its sufferers to others through the airway. 48 The results of the study showed that 23 (8.2%) respondents were smokers, and all were male.…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare workers who work in the pulmonary disease service units have a fourfold increased risk of LTBI compared to the non-clinical service units. 47 This is related to the characteristics of pulmonary TB, which is easily transmitted from its sufferers to others through the airway. 48 The results of the study showed that 23 (8.2%) respondents were smokers, and all were male.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the borderline group was composed almost entirely of women. According to the literature, the male gender is a risk factor for active TB but this gender disparity has not been fully investigated for LTBI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to some epidemiological studies, an increased risk of infection is related to activities that involve close contact with TB patients and work in which aerosol-generating procedures (AGPs) are used. Workplaces with AGP, work duration, room size, and priority of contact with TB were also reported to be related to LTBI [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Although medical activities are known to be a risk and ineffective prevention, poor immunity (i.e., lack of an adequate Bacille Calmette-Guérin (BCG) vaccine) is considered a greater risk for having LTBI [ 20 ].…”
Section: Introductionmentioning
confidence: 99%